A Sectoral Overview on the Integrated Reporting Practices in Turkey - Gürsoy, Ayşegül; Erbuğa, Gökçe Sinem (International Journal of Contemporary Economics and Administrative Sciences, 2024)
In Turkey, it has become an obligatory practice for companies listed in Borsa Istanbul (BIST), brokerage firms and portfolio management companies to make financial reporting in the period starting from 2005. Financial reporting means that companies share their financial information in order to support decision-making processes for both current and potential investors, fund holders and all kinds of creditors. Along with financial reporting, the results obtained regarding the economic activities of the companies and the results of these activities are shared with the public. Today, it is seen that investor expectations regarding companies are not only economic and an understanding that takes into account the environmental and social effects of companies has been adopted. As a result, it is possible for companies to integrate non-financial reporting practices into their existing financial reporting processes and make integrated reporting. Integrated reporting provides financial information users with information about the financial status of companies, as well as their environmental impacts and social and corporate governance practices. Integrated reporting, which enables the information presented to financial information users to be more transparent and accurate, also ensures that corporate reporting is carried out in a healthier and more effective manner. In this study, the development process of integrated reporting both in the world and in Turkey has been discussed; and also the current situation has been determined. By examining the integrated reports published in Turkey on a sectoral basis, it has been observed that the number of integrated reports published over the years has increased. Key words: ESG, financial reporting, non-financial reporting, integrated reporting. JEL Codes: M41, O16